Discover a world of knowledge and community-driven answers at IDNLearn.com today. Discover comprehensive answers from knowledgeable members of our community, covering a wide range of topics to meet all your informational needs.
Sagot :
Let's evaluate each expression one by one in detail.
### Expression 5: [tex]\( g^5 - h^3 \)[/tex] where [tex]\( g = 2 \)[/tex] and [tex]\( h = 7 \)[/tex]
1. Calculate [tex]\( g^5 \)[/tex]:
[tex]\[ g^5 = 2^5 = 2 \times 2 \times 2 \times 2 \times 2 = 32 \][/tex]
2. Calculate [tex]\( h^3 \)[/tex]:
[tex]\[ h^3 = 7^3 = 7 \times 7 \times 7 = 343 \][/tex]
3. Subtract [tex]\( h^3 \)[/tex] from [tex]\( g^5 \)[/tex]:
[tex]\[ g^5 - h^3 = 32 - 343 = -311 \][/tex]
So, [tex]\( g^5 - h^3 = -311 \)[/tex].
### Expression 10: [tex]\( c^2 + d^3 \)[/tex] where [tex]\( c = 8 \)[/tex] and [tex]\( d = -3 \)[/tex]
1. Calculate [tex]\( c^2 \)[/tex]:
[tex]\[ c^2 = 8^2 = 8 \times 8 = 64 \][/tex]
2. Calculate [tex]\( d^3 \)[/tex]:
[tex]\[ d^3 = (-3)^3 = -3 \times -3 \times -3 = -27 \][/tex]
3. Add [tex]\( c^2 \)[/tex] and [tex]\( d^3 \)[/tex]:
[tex]\[ c^2 + d^3 = 64 + (-27) = 64 - 27 = 37 \][/tex]
So, [tex]\( c^2 + d^3 = 37 \)[/tex].
### Expression 11: [tex]\( a^2 \cdot b^6 \)[/tex] where [tex]\( a = \frac{1}{2} \)[/tex] and [tex]\( b = 2 \)[/tex]
1. Calculate [tex]\( a^2 \)[/tex]:
[tex]\[ a^2 = \left(\frac{1}{2}\right)^2 = \frac{1}{2} \times \frac{1}{2} = \frac{1}{4} \][/tex]
2. Calculate [tex]\( b^6 \)[/tex]:
[tex]\[ b^6 = 2^6 = 2 \times 2 \times 2 \times 2 \times 2 \times 2 = 64 \][/tex]
3. Multiply [tex]\( a^2 \)[/tex] and [tex]\( b^6 \)[/tex]:
[tex]\[ a^2 \cdot b^6 = \frac{1}{4} \times 64 = 16 \][/tex]
So, [tex]\( a^2 \cdot b^6 = 16 \)[/tex].
### Expression 12: [tex]\( (r - s)^3 + r^2 \)[/tex] where [tex]\( r = -3 \)[/tex] and [tex]\( s = -4 \)[/tex]
1. Calculate the difference [tex]\( r - s \)[/tex]:
[tex]\[ r - s = -3 - (-4) = -3 + 4 = 1 \][/tex]
2. Calculate [tex]\( (r - s)^3 \)[/tex]:
[tex]\[ (r - s)^3 = 1^3 = 1 \][/tex]
3. Calculate [tex]\( r^2 \)[/tex]:
[tex]\[ r^2 = (-3)^2 = (-3) \times (-3) = 9 \][/tex]
4. Add [tex]\( (r - s)^3 \)[/tex] and [tex]\( r^2 \)[/tex]:
[tex]\[ (r - s)^3 + r^2 = 1 + 9 = 10 \][/tex]
So, [tex]\( (r - s)^3 + r^2 = 10 \)[/tex].
In summary, the evaluated results for each expression are:
1. [tex]\( g^5 - h^3 = -311 \)[/tex]
2. [tex]\( c^2 + d^3 = 37 \)[/tex]
3. [tex]\( a^2 \cdot b^6 = 16 \)[/tex]
4. [tex]\( (r - s)^3 + r^2 = 10 \)[/tex]
### Expression 5: [tex]\( g^5 - h^3 \)[/tex] where [tex]\( g = 2 \)[/tex] and [tex]\( h = 7 \)[/tex]
1. Calculate [tex]\( g^5 \)[/tex]:
[tex]\[ g^5 = 2^5 = 2 \times 2 \times 2 \times 2 \times 2 = 32 \][/tex]
2. Calculate [tex]\( h^3 \)[/tex]:
[tex]\[ h^3 = 7^3 = 7 \times 7 \times 7 = 343 \][/tex]
3. Subtract [tex]\( h^3 \)[/tex] from [tex]\( g^5 \)[/tex]:
[tex]\[ g^5 - h^3 = 32 - 343 = -311 \][/tex]
So, [tex]\( g^5 - h^3 = -311 \)[/tex].
### Expression 10: [tex]\( c^2 + d^3 \)[/tex] where [tex]\( c = 8 \)[/tex] and [tex]\( d = -3 \)[/tex]
1. Calculate [tex]\( c^2 \)[/tex]:
[tex]\[ c^2 = 8^2 = 8 \times 8 = 64 \][/tex]
2. Calculate [tex]\( d^3 \)[/tex]:
[tex]\[ d^3 = (-3)^3 = -3 \times -3 \times -3 = -27 \][/tex]
3. Add [tex]\( c^2 \)[/tex] and [tex]\( d^3 \)[/tex]:
[tex]\[ c^2 + d^3 = 64 + (-27) = 64 - 27 = 37 \][/tex]
So, [tex]\( c^2 + d^3 = 37 \)[/tex].
### Expression 11: [tex]\( a^2 \cdot b^6 \)[/tex] where [tex]\( a = \frac{1}{2} \)[/tex] and [tex]\( b = 2 \)[/tex]
1. Calculate [tex]\( a^2 \)[/tex]:
[tex]\[ a^2 = \left(\frac{1}{2}\right)^2 = \frac{1}{2} \times \frac{1}{2} = \frac{1}{4} \][/tex]
2. Calculate [tex]\( b^6 \)[/tex]:
[tex]\[ b^6 = 2^6 = 2 \times 2 \times 2 \times 2 \times 2 \times 2 = 64 \][/tex]
3. Multiply [tex]\( a^2 \)[/tex] and [tex]\( b^6 \)[/tex]:
[tex]\[ a^2 \cdot b^6 = \frac{1}{4} \times 64 = 16 \][/tex]
So, [tex]\( a^2 \cdot b^6 = 16 \)[/tex].
### Expression 12: [tex]\( (r - s)^3 + r^2 \)[/tex] where [tex]\( r = -3 \)[/tex] and [tex]\( s = -4 \)[/tex]
1. Calculate the difference [tex]\( r - s \)[/tex]:
[tex]\[ r - s = -3 - (-4) = -3 + 4 = 1 \][/tex]
2. Calculate [tex]\( (r - s)^3 \)[/tex]:
[tex]\[ (r - s)^3 = 1^3 = 1 \][/tex]
3. Calculate [tex]\( r^2 \)[/tex]:
[tex]\[ r^2 = (-3)^2 = (-3) \times (-3) = 9 \][/tex]
4. Add [tex]\( (r - s)^3 \)[/tex] and [tex]\( r^2 \)[/tex]:
[tex]\[ (r - s)^3 + r^2 = 1 + 9 = 10 \][/tex]
So, [tex]\( (r - s)^3 + r^2 = 10 \)[/tex].
In summary, the evaluated results for each expression are:
1. [tex]\( g^5 - h^3 = -311 \)[/tex]
2. [tex]\( c^2 + d^3 = 37 \)[/tex]
3. [tex]\( a^2 \cdot b^6 = 16 \)[/tex]
4. [tex]\( (r - s)^3 + r^2 = 10 \)[/tex]
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Trust IDNLearn.com for all your queries. We appreciate your visit and hope to assist you again soon.